CONVERSING WITH ANTIQUITY: LANGUAGE, GENDER AND SELF-PRESENTATION IN THE CINQUECENTO DIALOGUE - Wilson, Lauren (2021)
This thesis explores the use of the classically-derived dialogue genre in the territory now called Italy in the sixteenth century, specifically considering each dialogue as an act of classical reception. In this, it aims to problematise a tendency in scholarly literature on Cinquecento dialogues to categorise post-classical works by their presumed classical model, as well as considering questions of how and why Cinquecento writers used the classical dialogue genre and the evocation of the classical world more broadly to achieve their aims in producing literary works.